2019
DOI: 10.32014/2019.2518-170x.103
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Vibration Effect on Genus Sacchromyces Yeast Population Development

Abstract: NAS RK is pleased to announce that News of NAS RK. Series of geology and technical sciences scientific journal has been accepted for indexing in the Emerging Sources Citation Index, a new edition of Web of Science. Content in this index is under consideration by Clarivate Analytics to be accepted in the Science Citation Index Expanded, the Social Sciences Citation Index, and the Arts & Humanities Citation Index. The quality and depth of content Web of Science offers to researchers, authors, publishers, and ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…They have found that acoustic vibration frequency can have both positive and adverse effects on yeast development. The study has also proved that the acoustic effect parameters should be optimally adjusted for yeast generation and primary fermentation (Karpenko et al, 2019).…”
Section: The Effects Of Ultrasound On Yeastmentioning
confidence: 84%
“…They have found that acoustic vibration frequency can have both positive and adverse effects on yeast development. The study has also proved that the acoustic effect parameters should be optimally adjusted for yeast generation and primary fermentation (Karpenko et al, 2019).…”
Section: The Effects Of Ultrasound On Yeastmentioning
confidence: 84%
“…Saccharomyces cerevisiae yeast from various strains was subjected to audible sound exposure at fixed frequencies. It has been established that sound processing could either enhance or impair the technological characteristics of brewer's yeast [43]. This depends primarily on the processing parameters and the frequency of the sound.…”
Section: Ultrasound and Audible Range Sound Processingmentioning
confidence: 99%